Pembuatan Plang Denah Lokasi, Petunjuk, dan POI sebagai Icon Promosi Desa Wisata Pulau Mubut Darat - Jhon Hericson Purba; Adlian Jefiza; Satria Bayu Aji; Muhammad Zainuddin Lubis; Wenang Anurogo; Tian Havwini; Nurul Fadilah (Pusat P2M Politeknik Negeri Batam, 2022)
Abstract—The natural charm of the small islands in Kepulauan Riau can definitely spoil visitors’ eyes and attract their attention to visit these islands. Pulau Mubut Darat, which is located in Sembulang, Batam, Riau Islands, has become one of several choices of beach tourism areas. However, in the management of tourist sites, the community and managers in particular have not been able to implement ideas and supporting facilities to satisfy the tourists who come to visit so the tourist area of ​​the island of Mubut Darat began to lose competitiveness with other areas. The observation results of the Politeknik Negeri Batam community service team found several ideas that could help improve promotion and tourist attraction on Mubut Darat. One of them is by making a location plan or POI information sign in the Mubut Darat area. The method of making this sign begins with taking pictures of the entire Mubut Darat island. Then, the location points of each building and the facilities available in each area will be mapped and labeled. With the information signpost of the location plan or POI, tourists will get complete information about Mubut Darat. The location plan or POI information sign is expected to be part of the tourist photo icon on Mubut Darat which can promote and attract of tourists to come.